Multilevel Analysis on the Contextual Effect of Village and Sociodemographic Factors on Neonatal Death in Karanganyar, Central Java - Sukoco, Amin; Salimo, Harsono; Dewi, Yulia Lanti Retno (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Globally, the number of neo